Histeria e psiquiatria no Brasil da Primeira República Hysteria and psychiatry under Brazil's First Republic - Sílvia Alexim Nunes (História, Ciências, Saúde: Manguinhos, 2010)
Problematiza o pensamento psiquiátrico brasileiro sobre a histeria nas primeiras décadas do século XX, momento de expansão de uma medicina social que se constituiu no bojo de uma biopolítica de gestão populacional. Para isso, esse pensamento é inserido no debate sobre a histeria nos grandes centros europeus no século XIX e que foi referência para a nascente psiquiatria brasileira dentro de um projeto reformador e preventivista que caracterizou a medicina brasileira da época. São abordados o trabalho do neurologista brasileiro Antônio Austregésilo (1876-1960), sua inserção nesse projeto e seu lugar no processo de desmembramento da histeria como categoria diagnóstica, no campo da psiquiatria, o que se deu ao longo da República Velha. The article problematizes Brazilian psychiatric thought on hysteria in the early decades of the twentieth century, a time when a biopolicy of population management was lending impetus to the growth of social medicine. This notion is situated within the context of the nineteenth-century debate on hysteria that took place in major European centers and served as the main reference for Brazil's fledgling field of psychiatry. The debate found expression in Brazilian psychiatric discourse as part of the era's project for medical reform and prevention in Brazil. The work of Brazilian neurologist Antônio Austregésilo (1876-1960) within this project is also addressed, since he played a fundamental role in dismantling hysteria as a diagnostic category in psychiatry, a process that continued through the entire Old Republic.